2011
DOI: 10.1007/s00027-011-0180-0
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium, nitrate and phytoplankton interactions in a freshwater tidal estuarine zone: potential effects of cultural eutrophication

Abstract: Nitrate and ammonium are the most important nitrogen sources for phytoplankton growth. Differential utilization of inorganic nitrogenous compounds by phytoplankton has been observed and may have significant impacts on primary productivity at local scales. We used enrichment experiments with natural phytoplankton populations from the freshwater tidal zone of the Guadiana estuary, a coastal ecosystem increasingly subjected to anthropogenic influences, to study the effects of nitrate and ammonium on N-consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(97 citation statements)
references
References 39 publications
4
84
1
5
Order By: Relevance
“…Similar reports of dichotomous use of different forms of N have been frequently reported. Glibert et al (2004) reported the same phenomenon from Florida Bay, as did Domingues et al (2011) for a tidal fresh estuary. Similar observations have been reported from mesocosm experiments variably enriched with different forms of N (e.g.…”
Section: Seasonal Phytoplankton Distributionmentioning
confidence: 53%
“…Similar reports of dichotomous use of different forms of N have been frequently reported. Glibert et al (2004) reported the same phenomenon from Florida Bay, as did Domingues et al (2011) for a tidal fresh estuary. Similar observations have been reported from mesocosm experiments variably enriched with different forms of N (e.g.…”
Section: Seasonal Phytoplankton Distributionmentioning
confidence: 53%
“…The most common way of adding nutrient is adding a finite supply of dissolved nutrients as the setting concentrations at the beginning of the experiment and adding no more nutrients during the process of phytoplankton incubation (Domingues et al 2011;Ma et al 2015a, b;Paerl et al 2011;Xu et al 2010Xu et al , 2015. However, there are some problems with this approach.…”
Section: Discussionmentioning
confidence: 99%
“…This observation helped explain why the threshold of NH 4 -N was lower than the threshold of NO 3 -N. What is more, the relative preference for ammonium or nitrate is phytoplankton group-specific. In particular, cyanobacteria, chlorophytes, and chrysophytes prefer ammonium, while nitrate is preferred by diatoms, cryptophytes, and dinoflagellates (Chaffin and Bridgeman Domingues et al 2011;Donald et al 2011Donald et al , 2013Ohashi et al 2011). Cyanophytes and chlorophytes account for a very large proportion in Miyun Reservoir in July and August (Fig.…”
Section: Nutrient Thresholds Needed For Controlling Algal Blooms In Tmentioning
confidence: 99%
“…This higher uptake is attributed to differences in algal communities that occur in response to the supply of nitrate and ammonium, even at nitrogen concentrations considered saturating for algal growth (Glibert et al 2016 and references therein). Studies have suggested that diatoms thrive in nitrate-rich systems, whereas chlorophytes and cyanobacteria are often associated with ammonium-rich systems (e.g., Blomqvist et al 1994;Hyenstrand et al 1998;Glibert and Berg 2009;McCarthy et al 2009;Domingues et al 2011). Experimental manipulations conducted using algae and water from the Delta reproduced these observations .…”
Section: The Ammonium Paradoxmentioning
confidence: 87%